A study of lexical richness in ESL students’ writing / Josephine Uma Selvaraju - Josephine Uma , Selvaraju (2019)
The significance of the English language carries endless practicability which is known as commonly spoken language in major areas in Malaysia. The relationship between English language vocabulary and writing considered as notion in second language learning. This study aims to look at the lexical richness of Pre University students in their written context to ascertain if lexical richness has an impact on the quality of written essays. This study aims to investigate lexical richness produced by Foundation in Science students in two different semesters such as the first semester and final semester. Data gathered from two groups with a total of 30 numbers of participants and measured using Compleat Lexical Tutor through Vocabprofile by (Cobb, 2009). The lexical investigation is looking at 3 lexical richness categories; lexical variation, lexical density, and lexical sophistication. Lexical variation with the highest TTR value showed the ability to write the essay precisely without repetition of words that used more than once. Lexical density, three students have produced more than 50 % which shows the text is moderately high and has a good sense of writing and expressed ideas cohesive in a text. Lexical sophistication indicates that a higher percentage of high-frequency words showed a lower dimension of performance. Though, there was no much critical diverse between lexical variation, lexical density, and lexical sophistication among the first and final semesters.